Новые виды инфузорий рода Mantoscyphidia (Ciliophora, Peritricha) от пресноводных моллюсков - Бошко, Е.Г. (Вестник зоологии, 1993)
3 species are described as new: Af. radixi sp. n. found on gastropods Lymnaea (Radix) auricularia, L. (Peregriana) ovata (type locality: river Stugna, Kiev vicinity); Af. theodoxis sp. n.—on Theodoxus fluviatilis, Th. paliasi and Th. «pal~ lasi» gr. sp. (type locality river Stugna, Kiev vicinity); Af. sphacriidarum sp. n.—on bivalve Shadinicyclas rivicola (type locality: a Dnieper bay in Kiev vicinity). Fixed materials are deposited in the Schmalhausen Institute of Zoology (Kiev).